Conceptual design and analysis of a car bumper using finite element method. Issue 1 (1st January 2021) - G Keni, Laxmikant; Singh, Vaibhav; Singh, Navjoth; Thyagi, Akash; Kalburgi, Sagar; K N, Chethan
Abstract: Due to intrinsic or extrinsic conditions, the number of car accidents has increased currently across the globe. Drivers must be assured that they can avoid these problematic conditions. According to the statistics, about 10, 000 are dead, and more than a million people are wounded each year in India. Hence, improvement in the safety of vehicles is of utmost importance to shoot down the number of accidents. The automotive bumper beam is one of the essential components in passenger cars. Bumper beams reduce or minimize the extent of impact caused at the front and rear ends during a collision in passenger vehicles. It absorbs the impact energy. The important physical parameters in the bumper beams such as material, size, and design to improve the extent of crashworthiness are studied and discussed in this current work. Comparative analysis between 2 mm thickness and 4 mm thickness bumper with honeycomb structure is studied. An ideal design composition is considered. This helps in advanced safety precautions.